Karakterisasi Biokimia Aeromonas hydrophila dan Potensinya Sebagai Pemacu Pertumbuhan Bibit Tanaman Melon Emas - I KETUT SIADI; KHAMDAN KHALIMI; DEWA NYOMAN NYANA (Fakultas Pertanian Universitas Udayana, 2014)
Biochemical Characterization of Aeromonas hydrophila and Its Potential for Growth Stimulatorof Golden Melo Seedlings.The results showed that this research got 20 nitrogen fix bacteria isolate,However, Pg2 isolate could increase the growth of golden melo. The treatment with Pg2 isolatesignificantly increased the golden melo growth. All the plant growth parameters of treated plants weresignificantly higher than those of un-treated control plants (P<0.05). The leaf chlorophyll content, plantgrowth rate, and fresh and dry weights of plant were significantly higher than those of un-treatedcontrol plants. Isolates identified as Enterobacter cloacae PG2 percentage of 98.05% probability.